Minimally invasive pancreatoduodenectomy is associated with lower morbidity compared to open pancreatoduodenectomy: An updated meta-analysis of randomized controlled trials and high-quality nonrandomized studies. Issue 32 (August 2019) - Yan, Jia-fei; Pan, Yu; Chen, Ke; Zhu, He-pan; Chen, Qi-long
Abstract: Background: Minimally invasive pancreatoduodenectomy (MIPD) is being increasingly performed as an alternative to open pancreatoduodenectomy (OPD) in selected patients. Our study aimed to present a meta-analysis of the high-quality studies conducted that compared MIPD to OPD performed for pancreatic head and periampullary diseases. Methods: A systematic review of the available literature was performed to identify those studies conducted that compared MIPD to OPD. Here, all randomized controlled trials identified were included, while the selection of high-quality, nonrandomized comparative studies were based on a validated tool (i.e., Methodological Index for Nonrandomized Studies). Intraoperative outcomes, postoperative recovery, oncologic clearance, and postoperative complications were also evaluated. Results: Sixteen studies matched the selection criteria, including a total of 3168 patients (32.1% MIPD, 67.9% OPD). The pooled data showed that MIPD was associated with a longer operative time (weighted mean difference [WMD] = 80.89 minutes, 95% confidence interval [CI]: 39.74–122.05, P < .01), less blood loss (WMD = −227.62 mL, 95% CI: −305.48 to −149.75, P < .01), shorter hospital stay (WMD = −4.68 days, 95% CI: −5.52 to −3.84, P < .01), and an increase in retrieved lymph nodes (WMD = 1.85, 95% CI: 1.33–2.37, P < .01). Furthermore, the overall morbidity was significantly lower in the MIPD group (OR = 0.67, 95% CI: 0.54–0.82, P < .01), as were total postoperative pancreatic fistula (POPF) (OR = 0.79, 95% CI: 0.63–0.99, P = .04), delayed gastric emptying (DGE) (OR = 0.71, 95% CI: 0.52–0.96, P = .02), and wound infection (OR = 0.56, 95% CI: 0.39–0.79, P < .01). However, there were no statistically significant differences observed in major complications, clinically significant POPFs, reoperation rate, and mortality. Conclusion: Our study suggests that MIPD is a safe alternative to OPD, as it is associated with less blood loss and better postoperative recovery in terms of the overall postoperative complications as well as POPF, DGE, and wound infection. Methodologic high-quality comparative studies are required for further evaluation. Abstract : Supplemental Digital Content is available in the text